Bronchial hygiene techniques in patients on mechanical ventilation: what are used and why? - Evangelista Matilde, Isabela Naiara; Caserta Eid, Raquel Afonso; Nunes, Andreia Ferreira; Pepe Ambrozin, Alexandre Ricardo [UNESP]; Moura, Renata Henn; Carnieli-Cazati, Denise; Timenetsky, Karina Tavares (Inst Israelita Ensino & Pesquisa Albert Einstein, 2018)
Objective: To analyze and describe the maneuvers most commonly used in clinical practice by physical therapists and the reasons for choosing them. Methods: A prospective multicenter study using a questionnaire. The sample consisted of physical therapists from five hospitals (three private hospitals, a teaching hospital and a public hospital). Results: A total of 185 questionnaires were filled in. Most professionals had graduated 6 to 10 years before and over had over 10 years of intensive care unit experience. The most often used maneuvers were vibrocompression, hyperinflation, postural drainage, tracheal suction and motor mobilization. The most frequent reason for choosing these maneuvers was I notice they are more efficient in clinical practice. Conclusion: Physical therapy is mostly based on individual experience acquired in the clinical practice, and not on the scientific literature.
Keywords: Respiration, artificial; Physical therapy modalities; Physical therapy department, hospital; Evidence-based medicine